Perlindungan Hukum Terhadap Konsumen Pemenang Lelang di Lembaga Perbankan Kota Padang - Elfiawinda, Elfiawinda; Yaswirman, Yaswirman; Nurdin, Zefrizal (Universitas Ekasakti, 2023)
Society and banks are two components that need each other. Banks run businesses to make a profit. Like conventional banks which earn profits through interest on loans from debtors. Banks provide loans, but must also guarantee the repayment of the capital lent to debtors by binding the loan with mortgage rights. When the debtor is unable to pay the debt and is declared in default, the bank as the winner of the mortgage right has the right to sell the collateral with the mortgage right, submitting an auction request to the KPKNL. The auction winner is the bidder with the highest price. Auction winners often have difficulty controlling the auction object, because the debtor does not accept the auction results and makes various efforts to maintain the collateral, one of which is by filing an unlawful act lawsuit with the district court. The problem in this thesis is: What is the legal certainty of the transfer of ownership of mortgage objects through auction? What is the legal protection for the winner of the auction for the execution of mortgage rights filed as a party in a lawsuit against the law in terms of the Consumer Protection Law? What are the efforts of the auction winner in dealing with the plaintiff as debtor? The method used in this research is Sociological Juridical, the type of data collected is secondary and primary data, the data collection method is interviews and the nature of the research is descriptive. The research results obtained. 1) The transfer of rights through an auction occurs when the auction minutes are published which function as the basis for rights, but the transfer of rights only occurs on paper, because the auction winner cannot control the object. 2) The Consumer Protection Law guarantees that consumers get their rights, but what happens is that business actors often transfer or even eliminate responsibilities by having standard agreements which are actually prohibited by law. 3) The winner of the auction as a consumer, in facing the debtor's demands, tries to defend his rights, the losses arising from the demands from the debtor are the burden of the consumer himself, the business actor, in this case the bank, is not responsible for the losses suffered by the consumer, under the pretext of the object of the auction what has been purchased by the consumer, namely the auction winner, is at a low price, so that the loss becomes the burden of the auction winner.